Retrospective Studies with Small Sample Size are Still Dominating Colon Cancer Research: Local Recurrence in Right Sided Colon Cancer as a Case in Point - Khan, Yusra; Teng, Zhi Sean; Sayyed, Raza; El-Hussuna, Alaa (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Khan Y, Teng ZS, Sayyed R, El-Hussuna A. Retrospective studies with small sample size are still dominating colon cancer research: Local recurrence in right sided colon cancer as a case in point. Turk J Gastroenterol. 2025;36(5):333-335.